MEDICATION ERRORS IN PEDIATRICS AND PREVENTION STRATEGIES: AN INTEGRATIVE REVIEW - Bárbara Monteiro Volpatto; Wiliam Wegner; Luiza Maria Gerhardt; Eva Neri Rubim Pedro; Silvana da Silva Cruz; Larissa Edom Bandeira (Universidade Federal do Paraná, 2017)
An integrative review was undertaken to analyze the strategies, safety incidents and the phase of the medication process intended to prevent adverse events in pediatrics. Data collection took place between November/2015 and February/2017 in the databases: Latin American Literature in Health Sciences, Cumulative Index of Nursing and Allied Health Literature, U.S. National Library of Medicine and Web of Science. The following descriptors were used: medication errors, patient safety and child. Twenty-seven articles were selected, published between 2004 and 2016. The most investigated phase of the medication process was the drug prescription. The safety incident rates varied between 0.91% and 54%. No methodological standardization could be identified in the studies. The reported prevention strategies were: use of electronic drug prescription, clinical simulation, dosing protocol and incident reports. It is important for the risk identification and planning of prevention strategies to support the global analysis of the medication process.